CeO2 nano-enzyme with controllable surface performance as well as preparation method and application of CeO2 nano-enzyme
CeMOFs were synthesized by direct pyrolysis solvent-free method and heat-activated treatment to prepare CeO2 nanoenzymes with high phosphatase-like activity, which solved the problem of difficult control of the surface properties of CeO2 nanomaterials, achieved the improvement of its phosphatase-like catalytic activity, and provided a sensitive colorimetric method for the detection of organophosphate-like compounds.
Patent Information
- Application Number
- CN202411665075.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
AI Technical Summary
The existing CeO2 nanomaterials have problems with difficult surface properties in terms of catalytic properties, which affects their phosphatase-like catalytic properties.
CeMOFs were synthesized by direct pyrolysis solvent-free method, and CeO2 nanoenzymes with high phosphatase-like activity were prepared, and their surface properties were regulated by thermal activation treatment.
Controllable modulation of CeO2 surface properties is achieved, its phosphatase-like catalytic activity is improved, and a sensitive colorimetric method is provided for the detection of organophosphate compounds in food and environmental water samples.
Smart Images

Figure CN119500098A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanomaterials, and in particular to a CeO2 nanozyme with controllable surface properties, a preparation method and applications thereof. Background Art
[0002] Organophosphorus pesticides (OPs) have threatened food safety and environmental safety. Among them, organophosphate compounds, including nerve agents and organophosphorus pesticides, can rapidly inhibit the activity of acetylcholinesterase, have lasting effects on the environment, and threaten human health. Enzyme-mediated dephosphorylation reactions are considered to be an effective method for detecting organophosphate compounds and can specifically hydrolyze them into low-toxic molecules. However, the separation and purification cost of natural enzymes (such as organophosphate hydrolases, organophosphorus hydrolases, etc.) is high, the stability is low, and the storage resistance and recyclability are relatively poor, which limits their effectiveness in a wide range of applications. In order to overcome these challenges, nanozymes have received widespread attention.
[0003] There are relatively few reports on nanomaterials with phosphatase-like catalytic properties, mainly including Zr-based and Zn-based MOFs, Co3O4 / rGO, Co / 3DNG-2, CeO2, etc. Among them, CeO2 not only exhibits a variety of enzyme activities, but also has the advantages of low biotoxicity, high biocompatibility, structural stability and low cost, and is therefore regarded as one of the most promising nanozymes. However, the surface properties of CeO2 are the key factors affecting its phosphatase-like catalytic properties. Oxygen vacancy concentration and Ce 3+ / Ce 4+ The ratio of Ce is used as an important indicator to characterize its catalytic performance. These sites are mainly generated by structural defects. Although there are many synthetic strategies (hydrothermal method, solvothermal method and template-assisted method, etc.) as well as chemical doping and post-treatment methods to control oxygen vacancies and Ce 3+ However, the prepared CeO2 particles often have problems such as lack of pores, uneven morphology, and exposure of multiple types of crystal faces, which limits their catalytic activity and selectivity. Therefore, it is still urgent to develop a simple and effective method to achieve controllable modulation of CeO2 surface properties. Summary of the invention
[0004] The purpose of the present invention is to provide a CeO2 nanozyme with controllable surface properties, a preparation method and an application thereof, which synthesizes CeMOFs by a direct pyrolysis solvent-free method to prepare CeO2 with high phosphatase-like activity, providing a sensitive colorimetric method for evaluating the degree of organic phosphorus contamination of food and environmental water samples.
[0005] The embodiments of the present invention are achieved through the following technical solutions:
[0006] First, the present invention provides a method for preparing a CeO2 nanozyme with controllable surface properties, comprising the following steps:
[0007] (1) Preparation of CeMOFs precursors using a solvent-free method;
[0008] (2) The CeMOFs precursor is thermally activated to obtain CeO2 nanozymes with controllable surface properties.
[0009] More specifically, the preparation method of the CeMOFs precursor includes the following steps: mixing the Co salt and H3BTC and grinding them for a period of time to fully mix them; then, heat-treating the resulting mixture, naturally cooling it to room temperature, washing, separating and drying it to obtain the CeMOFs precursor.
[0010] The preparation method of CeO2 nanozyme specifically includes the following steps: placing a porcelain boat containing CeMOFs precursor in the insulation zone of a tubular furnace, gradually increasing the temperature and keeping it warm for a period of time under an air atmosphere, and naturally cooling it to room temperature to obtain CeO2 nanozyme.
[0011] Furthermore, the Co salt includes but is not limited to: cobalt nitrate, cobalt chloride or cobalt sulfate, and Co(NO3)2·6H2O is preferably selected.
[0012] Furthermore, the molar ratio of the Co salt to H3BTC is 1.5 to 3.5:1.
[0013] Furthermore, during the heat treatment, the heat treatment temperature is 80 to 150° C. and the heat treatment time is 10 to 15 hours.
[0014] Furthermore, during the gradient heating, the temperature is raised to 300-450° C. at a rate of 5° C. / min and maintained for 1-3 h.
[0015] Secondly, the present invention provides a CeO2 nanozyme prepared by the above preparation method; wherein the Ce in the CeO2 3+ The content of Ce 3+ With Ce 4+ The total content is 18% to 45%, preferably 35.02%.
[0016] Thirdly, the present invention provides an application of the above-mentioned CeO2 nanozyme in the detection of organophosphate compounds.
[0017] Specifically, the detection method of organophosphate compounds is: add the test solution and CeO2 nanozyme to the Tris-HCl buffer solution and mix well. After incubation for a period of time, measure the UV-visible absorbance of the reaction solution; substitute the measured absorbance data into the linear equation of absorbance and organophosphate compound concentration to obtain the concentration of organophosphate compounds in the test solution.
[0018] The technical solution of the embodiment of the present invention has at least the following advantages and beneficial effects:
[0019] 1. The present invention successfully synthesized CeMOFs by direct pyrolysis and solvent-free method, and then prepared CeO2 with high phosphatase-like activity; this is attributed to the high concentration of Ce on the surface of CeO2. 3+ (35.02%) and Ce 4+ site (oxygen vacancies, 35.19%), suitable Ce 3+ / Ce 4+ The ratio of CeO2 and the fully exposed (111) highly active crystal facets facilitate the adsorption and activation of water molecules and OPs molecules. Specifically, H2O and p-NPP are adsorbed on the CeO2 surface. 3+ Site and Ce 4+ site (oxygen vacancy); under alkaline conditions, Ce 3+ Activate H2O to decompose and generate -OH, which is then adsorbed on Ce 4+ The phosphorus-oxygen bond at the site is activated; at this time, the surface hydroxyl group and physically adsorbed water can act as nucleophiles to attack the P center of disodium nitrophenyl phosphate (p-NPP), resulting in its rapid hydrolysis to form p-nitrophenol and phosphate.
[0020] 2. The present invention constructs a colorimetric sensor based on CeO2 for sensitive detection of methylparaoxon. This method has a wide linear response range (0.005-25 mg / L) and a low detection limit. This work not only expands the preparation strategy of performance-controllable metal oxide nanozymes, but also provides a sensitive colorimetric method for evaluating the degree of contamination of food and environmental water samples by methylparaoxon. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a characterization spectrum of CeMOFs prepared in Example 1 of the present invention, wherein Figure 1 (a) Figure 1 (b) SEM images of CeMOFs under low and high magnification, respectively. Figure 1 (c) is the XRD spectrum of CeMOFs. Figure 1 (d) FT-IR spectra of H3BTC and CeMOFs;
[0022] Figure 2 (a) is the thermogravimetric curve and thermogravimetric differential curve of CeMOFs prepared in Example 1 of the present invention in air atmosphere; Figure 2 (b) is the phosphatase-like activity diagram of CeO2 calcined at different temperatures;
[0023] Figure 3Characterization spectra of CeO2 prepared at different calcination temperatures, where Figure 3 (a) is the XRD pattern of CeO2. Figure 3 (b) is the FT-IR spectrum of CeO2. Figure 3 (c) is the Raman spectrum of CeO2 excited at 405nm. Figure 3 (d)-(f) are the XPS graphs of the chemical composition of CeO2 and its elemental valence analysis (Ce 3d, O 1s, C 1s);
[0024] Figure 4 This is a SEM image of CeO2 obtained in Example 1 of the present invention, wherein Figure 4 (a) Figure 4 (b) SEM images of CeMOFs under low and high magnification, respectively. Figure 4 (c) Figure 4 (d) is a TEM image of CeO2 prepared in Example 1 of the present invention under low and high magnification microscopes, Figure 4 (e) is the HRTEM image of CeO2 obtained in Example 1 of the present invention, Figure 4 (f)- Figure 4 (i) are mapping diagrams of element distribution (Ce-OC, Ce, O and C elements) of CeO2 prepared in Example 1 of the present invention;
[0025] Figure 5 (a) is the adsorption-desorption isotherm diagram of the CeMOFs precursor and CeO2-350 nanozyme prepared in Example 1 of the present invention, Figure 5 (b) is a pore size distribution curve of the CeMOFs precursor and CeO2-350 nanozyme prepared in Example 1 of the present invention;
[0026] Figure 6 (a) is a comparison of the phosphatase-like activities of CeMOFs and CeO2 prepared at different temperatures. Figure 6 (b) Different concentrations of CeO2 and A 402 The relationship diagram, Figure 6 (c) Figure 6 (d) The relative catalytic activity of CeO2-350 at different reaction temperatures and pH values;
[0027] Figure 7 (a) is a graph showing the storage stability of CeO2 obtained in Example 1 of the present invention. Figure 7 (b) is a graph showing the catalytic activity results of different CeO2 prepared in Examples 1-6;
[0028] Figure 8(a)-(c) are the results of the effects of pH value, reaction time and CeO2 material concentration on the activity of CeO2-350 in degrading methyl paraoxon;
[0029] Fig. 9 (a) is the UV-visible absorption spectra and photos of the reaction solutions with different methyl paraoxon concentrations (inset in the upper left corner). Fig. 9 (b) is the linear fitting curve of methyl paraoxon, Fig. 9 (c) is a diagram showing the selectivity experimental results of methyl paraoxon detection. Fig. 9 (d) is the result of the anti-interference experiment of common anions and cations on the detection of methyl paraoxon. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0031] The following is a detailed description of a CeO2 nanozyme with controllable surface properties, a preparation method and an application thereof provided in an embodiment of the present invention.
[0032] A method for preparing a CeO2 nanozyme with controllable surface properties comprises the following steps:
[0033] (1) Preparation of CeMOFs precursor using a solvent-free method: Co salt and H3BTC are mixed and ground for a period of time to make them fully mixed; then, the resulting mixture is reacted in an oven at 80-150°C for 10-15h, cooled naturally to room temperature, washed, separated and dried to obtain a CeMOFs precursor;
[0034] Wherein, the Co salt includes but is not limited to: cobalt nitrate, cobalt chloride or cobalt sulfate, preferably Co(NO3)2·6H2O; the molar ratio of the Co salt to H3BTC is 1.5 to 3.5:1;
[0035] (2) thermally activating the CeMOFs precursor: placing the ceramic boat containing the CeMOFs precursor in the heat preservation zone of the tube furnace, heating the temperature to 300-450°C at a rate of 5°C / min in an air atmosphere, and keeping the temperature for 1-3 hours. After cooling naturally to room temperature, the CeO2 nanozyme is obtained. 3+ The content of Ce 3+ With Ce 4+ The total content is 18% to 45%, preferably 35.02%.
[0036] The present invention also provides an application of the CeO2 nanozyme obtained above in the detection of organic phosphate compounds; the organic phosphate compounds can be: methyl paraoxon, 2-hydroxypropyl p-nitrophenyl phosphate, p-nitrophenyl phosphate disodium, 4-methylumbelliferyl phosphate disodium salt, phenoxy 1,2-dioxetane, bis-p-nitrophenyl phosphate, etc. The present invention is introduced in detail with the detection of methyl paraoxon. Specifically, the detection method of methyl paraoxon is: adding a test solution and CeO2 nanozyme to a Tris-HCl buffer solution and mixing, incubating for a period of time, and measuring the ultraviolet visible absorbance of the reaction solution; substituting the measured absorbance data into the linear equation of absorbance and methyl paraoxon concentration, that is, obtaining the methyl paraoxon concentration in the test solution.
[0037] Furthermore, the pH value of the buffer solution is 9.5-12, the reaction time is 1.5-2.5h, and the concentration of CeO2 nanozyme is 1.5-2mg / mL. Preferably, the pH value of the buffer solution is 10, the reaction time is 2h, and the concentration of CeO2 nanozyme is 2mg / mL.
[0038] Further, the absorbance is the absorbance at 402 nm (A 402 ).
[0039] Furthermore, the linear equation is: y=0.0725x+0.007(R 2 =0.9991), and its detection limit (LOD) was as low as 2 μg / L; where x represents the concentration of methyl paraoxon and y represents the absorbance at 402 nm (A 402 ).
[0040] The present invention first prepares CeMOFs and then pyrolyzes them to prepare the derived metal oxide CeO2, which not only inherits the large specific surface area and high porosity of MOFs, but also generates uniform and abundant active sites; however, in the prior art, most MOFs are still synthesized by solvothermal method. In practice and research, the inventors considered the large amount of waste liquid and the possible use of dangerous regulators (such as hydrofluoric acid (HF)) in this method, so they used a solvent-free synthesis method to prepare CeMOFs precursors, and obtained CeO2 nanozymes with controllable surface properties and high phosphatase-like activity by pyrolysis, which is attributed to the high concentration of Ce on the surface of CeO2. 3+ and oxygen vacancies, suitable Ce 3+ / Ce 4+ The high ratio and fully exposed highly active crystal faces make it conducive to the adsorption and activation of water molecules and OPs molecules.
[0041] The present invention analyzes the structural and component evolution of CeO2 during pyrolysis, and studies the phosphatase-like catalytic performance of the obtained CeO2 using p-NPP as a model substrate. It shows that the mechanism of CeO2 catalyzing the hydrolysis of p-NPP can be summarized as follows: First, H2O and p-NPP are adsorbed on the CeO2 surface, respectively. 3+ Site and Ce 4+ site (oxygen vacancy); under alkaline conditions, Ce 3+ Activate H2O to decompose and generate -OH, which is then adsorbed on Ce 4+ The phosphorus-oxygen bond at the site is activated; at this time, the surface hydroxyl group (-OH) and physically adsorbed water can act as nucleophiles to attack the P center of p-NPP, resulting in its rapid hydrolysis to produce p-nitrophenol and phosphate; subsequently, a colorimetric detection sensor for methyl paraoxon was constructed based on CeO2. Through the study of its detection performance and application characteristics, it was verified that the detection method has a wide linear response range (0.005-25 mg / L) and a low detection limit (3σ, 2 μg / L); this provides a sensitive colorimetric method for assessing the degree of methyl paraoxon contamination in food and environmental water samples, demonstrating its application potential in the field of OPs sensing.
[0042] Example 1
[0043] This embodiment provides a method for preparing CeO2 nanozyme, comprising the following steps:
[0044] (1) 3 mmol Ce(NO3)3·6H2O and 1.5 mmol H3BTC were added to a mortar and ground for 10 minutes to fully mix to obtain a mixture; then, the obtained mixture was transferred to a 20 mL glass sample bottle with a cover and reacted in an oven at 100°C for 12 hours; after naturally cooling to room temperature, it was washed with 30 mL ethanol and 60 mL ethanol at 70°C for 4 hours, and then washed with 30 mL ethanol to fully remove the unreacted reagents; finally, the prepared sample was vacuum dried at 60°C to obtain CeMOFs;
[0045] (2) Take 200 mg of CeMOFs and spread it flat in a porcelain boat, place it in the insulation zone of a tubular furnace, heat it to 350 °C at 5 °C / min in an air atmosphere and keep it warm for 2 h. After naturally cooling to room temperature, CeO2 nanozyme was obtained, which was recorded as CeO2-350.
[0046] Embodiment 2-7
[0047] The difference between Examples 2-7 and Example 1 is that: in step (2), the calcinations are carried out at 300°C, 310°C, 320°C, 400°C, 450°C and 500°C, and the CeO2 nanozyme materials obtained in Examples 2-7 are respectively recorded as CeO2-300, CeO2-310, CeO2-320, CeO2-400, CeO2-450 and CeO2-500.
[0048] It should be noted that in the following experimental examples, unless otherwise specified, the CeO2 used was prepared by the preparation method of Example 1.
[0049] Experimental Example 1-Characterization of CeMOFs and CeO2
[0050] 1. This experimental example systematically characterizes the structure and surface properties of CeO2 using XRD and SEM. The scanning electron microscope images of CeMOFs synthesized in Example 1 at different magnifications are shown in Figure 1 (a) and Figure 1 (b) Figure 1 (a) and Figure 1 The results of (b) show that the CeMOFs precursor synthesized in Example 1 presents a flake structure or a three-dimensional structure formed by stacking flakes; Figure 1 The XRD results of (c) show that CeMOFs have diffraction peaks at 8.5°, 10.8° and 17.6°, indicating that it has the structural characteristics of MOF-76 and good crystallinity. Although the positions of the diffraction peaks of CeMOFs are similar to those reported in the literature, their intensities are different, and a new diffraction peak appears at 15.9°, which may be caused by differences in the synthesis method.
[0051] Figure 1 (d) shows the FT-IR spectrum of CeMOFs. Figure 1 (d) It can be seen that: 3424cm -1 The broad absorption peak at 3072 cm -1 The weak absorption peak at 1548 cm -1 The peaks at are attributed to the CH stretching vibration (ν(CH) ar ) and C=C stretching vibration (ν(C=C) ar );and at 1212cm -1 The peak at is the in-plane vibration of the C=C bond in the aromatic ring (δ(CCH) ar ), further confirming the existence of benzene-1,3,5-tricarboxylate linkers in CeMOFs. In addition, the -1 and 1396cm -1The peaks at correspond to COO - In addition, the C=O stretching vibration peak (1712cm -1 ) disappears after the synthesis of CeMOFs, while the -1 The stretching vibration peak of CH on the benzene ring (ν(CH)) is retained, which indicates that BTC and Ce 3+ A coordination reaction occurred between them.
[0052] Experimental Example 2-Thermal Stability
[0053] In order to evaluate the thermal stability of CeMOFs, thermogravimetric analysis was performed in air atmosphere. Figure 2 (a), where the black line is the thermogravimetric curve (TG) and the blue line is the differential thermogravimetric curve (DTG). Figure 2 (a) It can be seen that when the test temperature gradually increases from room temperature to 325°C, CeMOFs have almost no weight loss; this indicates that the thermal stability of CeMOFs is as high as 325°C, and no obvious phase change occurs below 325°C. When the temperature is further increased, the mass of the CeMOFs precursor begins to decrease, mainly due to the thermal decomposition of the organic ligands.
[0054] In addition, this experimental example also compares the absorbance of CeO2 materials (ie, Examples 1-7), CeMOFs precursors, and p-nitrophenyl phosphate disodium (p-NPP) at different calcination temperatures. Figure 2 (b) Figure 2 (b) It can be seen that the CeO2-350 nanozyme material prepared at 350°C exhibits the best phosphatase-like activity. Based on this, the subsequent experimental examples mainly focus on using CeO2-350 nanozyme materials and exploring the effect of calcination temperature on the surface properties of the material.
[0055] Experimental Example 3-Effect of Calcination Temperature on Material Surface Properties
[0056] This experiment first used XRD, FT-IR, Raman, XPS and other experimental methods to explore the effect of calcination temperature on the surface properties of CeO2. Figure 1 (c) and Figure 1(d) The XRD characterization results show that the diffraction peaks of CeO2-300 are basically consistent with those of CeMOFs. As the calcination temperature increases, the characteristic diffraction peaks of CeMOFs (2θ=10.6°, 15.9°) gradually disappear, indicating that the crystal structure of MOFs is destroyed. When the calcination temperature reaches 350°C, the characteristic diffraction peaks of the precursor completely disappear, and are replaced by new diffraction peaks (2θ=28.6°, 33.2°, 47.6°, 56.3°), which are consistent with the standard cards of CeO2, confirming the successful synthesis of CeO2. Further increasing the calcination temperature to 400°C, the diffraction peaks become sharper, indicating that the obtained CeO2 structure is more ordered.
[0057] FT-IR results are as follows Figure 3 As shown in (b), with the increase of calcination temperature, the degree of pyrolysis gradually increases, and the absorption peak of organic ligands in CeMOFs (ν(CH) ar , ν(CH)) disappear successively. In addition, when the calcination temperature exceeds 300℃, about 499cm -1 A new broad absorption band appears at , which corresponds to the stretching vibration of the O-Ce-O bond in cerium oxide (ν(O-Ce-O)). As the calcination temperature increases, the intensity of ν(O-Ce-O) gradually increases, indicating that the degree of oxidation of the material increases. In CeO2-350, ν(OH), ν as (COO - ) and ν s (COO - ) and other characteristic peaks, indicating the presence of carboxylate groups and abundant Ce-OH structures on its surface. It is worth mentioning that the terminal -OH group usually exhibits surface alkalinity, while Ce 4+ Then it has and Lewis acidic characteristics.
[0058] Figure 3 (c) shows the Raman spectrum of CeO2, 460 cm -1 、599cm -1 and 1176cm -1 The absorption bands at 2 and 3 correspond to the symmetric stretching vibration modes of the ceria fluorite phase (F 2g ), oxygen vacancy-related defect-induced modes (D) and second-order longitudinal photon modes (2LO). By calculating the intensity ratio I D / I F2g , the relative concentration of surface oxygen vacancies can be estimated, and the specific results are shown in Table 1. As the calcination temperature increases, the relative concentration of oxygen vacancies decreases, which is mainly due to the increase in the degree of oxidation of the precursor to CeO2. This result is consistent with the XPS analysis results ( Figure 3(d) and Table 1). According to literature reports, surface oxygen vacancies (i.e., Ce 4+ ) is the binding site for the phosphoryl oxygen in the organophosphorus. Therefore, with the increase of calcination temperature, the number of vacancies available for p-NPP binding decreases significantly. It is worth noting that the relative concentration of oxygen vacancies in CeO2-350 is still significantly higher than that of commercial CeO2 (CeO2-C, com-CeO), CeO2 prepared by precipitation method (CeO2-P) and other MOFs-derived CeO2 reported in most literature (see Table 1).
[0059] Table 1-Surface I of CeO2 from different sources D / I F2g , O v Concentration and Ce 3+ Comparison of concentration
[0060]
[0061]
[0062] The chemical composition and element valence state of CeO2 materials were further analyzed by XPS. Figure 3 As shown in (e), CeMOFs calcined at different temperatures contain Ce 4+ and Ce 3+ The XPS spectrum of Ce 3d can be fitted into five pairs of spin-orbit components, where U and V represent 3d5 / 2 orbital and 3d3 / 2 orbital, respectively. In the spectrum, the four peaks marked as U0, U', V0 and V' correspond to Ce 3+ The remaining six peaks represent the characteristic peaks of Ce 4+ The fitting results are shown in Table 1. As the calcination temperature increases, Ce 3+ This indicates that CeO2 calcined at different temperatures has different catalytic activities, which can be attributed to the Ce related to oxygen vacancies. 3+ Surface structural defects caused by species. In CeO2-350, Ce 3+ The content of Ce is 35.02% 3+ / (Ce 3+ +Ce 4+ )), significantly higher than the CeO2 reported in the literature. 3+ Participates in the adsorption and activation of water molecules and plays a key role in the hydrolysis reaction of phosphate bonds (PO). 3+ Too high a content may mean Ce 4+ The content is reduced, which will be unfavorable for the adsorption of p-NPP. Figure 3(f) The XPS spectrum fitting results of C 1s show two peaks at 284.8 eV and 288.68 eV, corresponding to C=C and O-C=O bonds, respectively, which further indicates that the surface of CeO2-350 is rich in carboxylate groups. 3+ / Ce 4+ The ratio not only ensures the effective adsorption of phosphate, but also provides sufficient hydrolysis active sites, which is beneficial to the catalytic reaction.
[0063] Experimental Example 4
[0064] In this experiment, SEM and TEM techniques were used to study the morphology of CeO2-350. Figure 4 The SEM images of (a)-(b) show that CeO2-350 basically maintains the flake structure of CeMOFs or the three-dimensional structure formed by stacking flakes. The material shrinks slightly and the surface roughness increases during the calcination process. Figure 4 TEM images (c)-(d) show that nanoparticles are evenly distributed in CeO2-350. Figure 4 The HRTEM image (e) reveals that two characteristic lattices are exposed in CeO2-350, with lattice spacings of 0.31nm and 0.19nm, which correspond to the (111) crystal plane and (220) crystal plane of CeO2, respectively. Among them, the (111) crystal plane is dominant, indicating that CeO2-350 exposes abundant (111) crystal planes. Figure 4 The element distribution maps of (f)-(i) show that Ce, O and C elements are uniformly distributed in CeO2-350. The above results show that Example 1 of the present invention successfully synthesized the CeO2-350 nanozyme material.
[0065] Experimental Example 5
[0066] This experimental example shows the adsorption-desorption isotherms and pore size distribution curves of the CeMOFs precursor and CeO2-350 nanozyme prepared in Example 1, respectively. Figure 5 (a) Figure 5 (b). Figure 5 The experimental results of (b) show that after calcination at 350 °C, the physical properties of CeMOFs are significantly improved, especially in terms of specific surface area and pore volume. The specific surface area and pore volume of the precursor CeMOFs are relatively small, which are 13.56 m 2 / g and 0.064cm 3 / g. After calcination, the specific surface area of CeO2-350 increased to 143.86m 2 / g, pore volume increased by 0.29cm 3 / g. Compared with CeMOFs, CeO2-350 has a tenfold increase in specific surface area and exhibits a rich mesoporous structure. This provides more accessible sites for substrate binding and reaction, which is crucial for enhancing catalytic activity. Taken together, these properties enable CeO2-350 to exhibit superior performance in catalytic applications.
[0067] Experimental Example 6
[0068] This experimental example is to explore the effects of different temperatures, different concentrations of CeO2, and pH on the catalytic activity of nanozymes;
[0069] The phosphate bond of the model substrate p-nitrophenyl phosphate (p-NPP) is cleaved by the phosphatase mimetic enzyme, and one of the products is yellow p-nitrophenol (p-NP) with a characteristic absorption peak at 402nm. In this study, CeMOFs, CeO2 and the model substrate p-NPP were mixed and reacted under specific conditions, and the phosphatase-like activity was evaluated by monitoring the characteristic spectrum of p-NP. Figure 2 (b) shows that in the system where p-NPP and CeO2 coexist, the characteristic absorption of p-NP is generated; while in the system containing only p-NPP or p-NPP and CeMOFs coexist, the characteristic absorption peak of p-NP is not observed. This result shows that the calcined CeO2 has phosphatase-like activity, and the calcination temperature plays an important role in improving the activity of nanozymes (see Figure 6 (a)). Among the various calcination temperatures, CeO2-350 prepared at 350 °C exhibited the best phosphatase-like activity, which was attributed to its abundant surface oxygen vacancies, Ce 3+ / Ce 4+ The ratio is closely related to the synergistic effect between the exposed highly active (111) crystal facets.
[0070] Similar to other nanozymes, the enzyme-like catalytic activity of CeO2-350 is regulated by factors such as material concentration, reaction temperature, and solution pH. Figure 6 (b) As the CeO2 material concentration increases from 20 to 300 μg / mL, the amount of p-NP generated continues to increase, and A 402 Considering that the quantitative basis of UV-visible spectrophotometry, Lambert-Beer's law, is applicable to dilute solutions, 150 μg / mL of CeO2-350 was selected for subsequent experiments. Figure 6 (c) shows that CeO2-350 exhibits phosphatase-like activity at different reaction temperatures (0-80°C), and the activity increases with increasing temperature. Based on practical application considerations, the present invention selects 37°C as the reaction temperature for subsequent experiments. Figure 6(d) shows that when the pH value is greater than 5, CeO2-350 exhibits obvious phosphatase-like activity, and its activity gradually increases with the increase of pH value.
[0071] Experimental Example 7
[0072] 7.1 Stability of Nanozymes
[0073] The stability of nanozymes is an important property that has attracted much attention. Therefore, Example 1 was used as an experimental object to investigate the storage stability of the CeO2 nanozyme material prepared in Example 1. The results are shown in Table 1. Figure 7 .Depend on Figure 7 (a) The results show that the CeO2 nanozyme material still maintains more than 94% of its activity after storage for 40 days, indicating that CeO2-350 has good storage stability.
[0074] 7.2 Reproducibility between different batches
[0075] Examples 1-6 were used as experimental objects to investigate the catalytic activity of 6 groups of CeO2 nanozymes. Figure 7 (b) Figure 7 (b) The results showed that the catalytic activity of CeO2 nanozymes between different batches remained stable, and the RSD between different batches was less than 1.84%, indicating that CeO2-350 nanozymes had good reproducibility.
[0076] Experimental Example 8 - CeO2 for Colorimetric Detection of Methyl Paraoxon
[0077] Based on the excellent phosphatase-like activity of CeO2, this experimental example uses CeO2-350 prepared in Example 1 to construct a colorimetric method for detecting methyl paraoxon. Similar to p-NPP, methyl paraoxon can be hydrolyzed to generate p-NP, which has a characteristic absorption peak at 402nm and appears yellow. In order to improve the sensing performance, the detection conditions such as pH, reaction time and nanozyme concentration were first optimized. The results are shown in Figure 2. Figure 8 As shown. Figure 8 The results show that when pH = 10, the reaction time is 2h and the nanozyme concentration is 2mg / mL, the catalytic activity of CeO2-350 towards methyl paraoxon reaches the best state.
[0078] Under the above optimal conditions, a colorimetric detection method for methyl paraoxon was constructed based on the phosphatase-like activity of CeO2-350. Fig. 9 As shown in (a), as the concentration of methyl paraoxon gradually increases in the range of 0 to 30 mg / L, the ultraviolet absorption spectrum of the detection system continues to enhance, and the reaction solution gradually changes from colorless to yellow. Fig. 9 (b) further shows that after the degradation of methyl paraoxon, the absorbance at 402 nm (A 402) showed a good linear relationship with the concentration of methyl paraoxon in the concentration range of 0.005 to 25 mg / L, and the linear equation was: y = 0.0725x + 0.0007 (R 2 =0.9991); wherein x represents the concentration of methyl paraoxon and y represents A 402 , and the detection limit (3σ) is as low as 2μg / L (i.e. 0.008μmol / L). Compared with other colorimetric methods or CeO2-based fluorescence methods reported in the literature, the results are shown in Table 2; from the results in Table 2, it can be seen that the detection method established in this experimental example has a lower detection limit and a wider linear range. Therefore, this method can not only degrade methyl paraoxon, but also has a high detection sensitivity.
[0079] Table 2 - Comparison of analytical performance of different optical sensors for detecting methyl paraoxon
[0080]
[0081]
[0082] In addition, in order to evaluate the application potential of the constructed method, we tested its selectivity and anti-interference ability. Fig. 9 As shown in (c), under the optimal conditions, after adding 10 mg / L methyl paraoxon, the 402 Obvious absorption was observed, and its intensity was much higher than that of other organophosphorus pesticides (such as methyl parathion, fenitrothion, glyphosate), chlorinated nicotinoid pesticides (such as acetamiprid) and carbamate pesticides (such as methomyl). This indicates that the method has excellent selectivity for the detection of methyl paraoxon. Fig. 9 (d) shows the effect of common anions and cations in environmental water samples on the detection signal. - 、NO3 - 、CO3 2- The concentration of Al 3+ 、Zn 2+ The concentration of Ca is 1 mM. 2+ The concentration is 0.5mM, PO4 3- The concentration is 0.25 mM. The results show that the influence of these common anions and cations on the detection signal is less than 5%, and it has good anti-interference ability. Therefore, the colorimetric method of the present invention has the potential to detect the level of methyl paraoxon in actual samples, and has high selectivity and excellent anti-interference ability.
[0083] In order to test the actual application performance of this detection method in methyl paraoxon, it was applied to the detection of methyl paraoxon in environmental water samples (Xihu Lake water and Fuhe River water, where Fuhe River water and Xihu Lake water were taken from Fuhe River and Xihu Lake next to Southwest Jiaotong University) and food samples. A certain concentration of methyl paraoxon standard solution was added to the actual sample, and the A 402 , and then calculate the concentration of the target compound and compare it with the spike concentration. The results are shown in Table 3. As shown in Table 3: The spike recovery of all samples ranged from 92.7% to 106.4%, and the RSD was less than 6%, which showed that the method had good accuracy and reproducibility. These research results fully demonstrated that the established method has good application potential in the detection of methyl paraoxon in actual samples.
[0084] Table 3 - Comparison of detection of methyl paraoxon in different actual samples
[0085]
[0086] Among them, *: mg / kg; ND: Not Detected.
[0087] In summary, the present invention successfully synthesized CeMOFs by direct pyrolysis and solvent-free method, and then prepared CeO2-350 with high phosphatase-like activity. This is attributed to the high concentration of Ce on the surface of CeO2-350. 3+ (35.02%) and oxygen vacancies (35.19%), suitable Ce 3+ / Ce 4+ The ratio and fully exposed highly active (111) crystal facets make it conducive to the adsorption and activation of water molecules and OPs molecules. The present invention constructs a colorimetric sensor for sensitive detection of methyl paraoxon based on CeO2-350. The method has a wide linear response range (0.005-25 mg / L) and a low detection limit (3σ, 2 μg / L). This work not only expands the preparation strategy of metal oxide nanozymes with controllable performance, but also provides a sensitive colorimetric method for evaluating the degree of contamination of food and environmental water samples by methyl paraoxon.
Claims
1. A method for preparing CeO2 nanozyme with controllable surface properties, characterized in that: The following steps are involved: (1) Preparation of CeMOFs precursors using a solvent-free method; (2) The CeMOFs precursor is thermally activated to obtain CeO2 nanozymes with controllable surface properties.
2. The method for preparing CeO2 nanozyme with controllable surface properties according to claim 1, characterized in that: The preparation method of the CeMOFs precursor comprises the following steps: mixing Co salt and H3BTC and grinding them for a period of time to fully mix them to obtain a mixture; then, heat-treating the obtained mixture, naturally cooling it to room temperature, washing, separating and drying it to obtain a CeMOFs precursor.
3. The method for preparing CeO2 nanozyme with controllable surface properties according to claim 2, characterized in that: The preparation method of the CeO2 nanozyme comprises the following steps: placing a porcelain boat containing a CeMOFs precursor in a tubular furnace insulation zone, gradually heating and insulating the zone for a period of time in an air atmosphere, and naturally cooling the zone to room temperature to obtain the CeO2 nanozyme.
4. The method for preparing CeO2 nanozyme with controllable surface properties according to claim 2, characterized in that: The Co salt is any one or more of cobalt nitrate, cobalt chloride or cobalt sulfate.
5. The method for preparing CeO2 nanozyme with controllable surface properties according to claim 2, characterized in that: The molar ratio of the Co salt to H3BTC is 1.5 to 3.5:
1.
6. The method for preparing CeO2 nanozyme with controllable surface properties according to claim 3, characterized in that: During heat treatment: the heat treatment temperature is 80-150°C, and the heat treatment time is 10-15h; during gradient heating, the temperature is increased to 300-450°C at a rate of 5°C / min and kept warm for 1-3h.
7. The method for preparing CeO2 nanozyme with controllable surface properties according to claim 2, characterized in that: Ce in the CeO2 nanozyme 3+ The content of Ce 3+ With Ce 4+ 18% to 45% of the total content.
8. A CeO2 nanozyme with controllable surface properties, characterized in that: The method is prepared according to any one of claims 1 to 7.
9. An application of CeO2 nanozyme with controllable surface properties, characterized in that: The CeO2 nanozyme prepared by the preparation method described in any one of claims 1 to 7 is used in the detection of organophosphate compounds.
10. The use of CeO2 nanozyme according to claim 9, characterized in that: The detection method of the organic phosphate compounds is as follows: adding the test liquid and CeO2 nanozyme to a buffer solution and mixing them evenly, incubating for a period of time, and then measuring the ultraviolet visible absorbance of the reaction solution; substituting the measured absorbance data into the linear equation of absorbance and organic phosphate compound concentration to obtain the concentration of organic phosphate compounds in the test liquid.
Citation Information
Cited By
Method for detecting glyphosate residues in coffee in dual modes of fluorescence and chemiluminescence
CN120253811A
Kit for detecting paraoxon organophosphorus pesticide in real time
CN120314291A